Answer: x = 2
Step-by-step explanation: If g(x) = 3x + 14, and g(x) = 20 also, you first can set 3x+14 = 20. To find the value of x, you want to isolate the variable. You can subtract 14 from both sides to get 3x = 6. Finally, to find out the value of x, divide 3 from both sides. This leaves you with x = 2. You can check this by plugging two back into the original equation 3 times 2 = 6, and 6 plus 14 equals 20.
Answer:
24
Step-by-step explanation:
Each Foot is 12 inches
Answer:
<h2>M(-6, 4)</h2>
Step-by-step explanation:
The formula of a midpoint of (x₁, y₁) and (x₂, y₂):
![M\left(\dfrac{x_1+x_2}{2},\ \dfrac{y_1+y_2}{2}\right)](https://tex.z-dn.net/?f=M%5Cleft%28%5Cdfrac%7Bx_1%2Bx_2%7D%7B2%7D%2C%5C%20%5Cdfrac%7By_1%2By_2%7D%7B2%7D%5Cright%29)
We have two points (-3, 7) and (-9, 1).
Substitute:
![x=\dfrac{-3+(-9)}{2}=\dfrac{-12}{2}=-6\\\\y=\dfrac{7+1}{2}=\dfrac{8}{2}=4](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B-3%2B%28-9%29%7D%7B2%7D%3D%5Cdfrac%7B-12%7D%7B2%7D%3D-6%5C%5C%5C%5Cy%3D%5Cdfrac%7B7%2B1%7D%7B2%7D%3D%5Cdfrac%7B8%7D%7B2%7D%3D4)
<u>Answer:
</u>
Required five terms of sequence are 19 , 12 , 5 , -2 and -9 .
<u>
Solution:
</u>
Need to find the five terms of the sequence.
Given recursive rule is f(x) = f(x-1) -7
Substituting x = 2 , f(2) = f(2-1)-7
= f(2) = f(1) – 7 ------(1)
Also given that f(2) = 12.
On substituting the given value of f(2) in eq (1) we get
12 = f(1) – 7
f(1) = 12 + 7 = 19
Using given recursive rule and given value of f(2) calculating f(3)
Substituting x = 3 ,
f(3) = f(3-1) – 7
= f(2) – 7
= 12 – 7
= 5
Using given recursive rule and calculated value of f(3) calculating f(4)
Substituting x = 4,
f(4) = f(4-1) – 7
= f(3) – 7
= 5– 7
= -2
Using given recursive rule and calculated value of f(4) calculating f(5)
Substituting x = 5,
f(5) = f(5-1) – 7
= f(4) – 7
= -2– 7
= -9
Hence required five terms of sequence are 19 , 12 , 5 , -2 and -9 .